Electrical characterization of nanocluster n-CdO/p-Si heterojunction diode - Yakuphanoğlu, Fahrettin; Caglar, Mujdat; Caglar, Yasemin; Ilican, Saliha (Elsevier Science Sa, 2010)
The nanocluster n-CdO/p-Si heterojunction diode was fabricated by sol-gel method. The structural and optical properties of the nanocluster CdO film have been investigated. The CdO film has a polycrystalline with a cubic monteponite phase. The scanning electron microscopy images indicate that the surface morphology CdO film is almost homogeneous and the CdO film is consisted of the clusters formed with coming together of the nanoparticles. The optical band gap of the CdO film was found to be 2.45 eV using optical absorption method. The electrical properties of the p-n heterojunction composed of transparent CdO and p-Si semiconductors were investigated by current-voltage and conductance-frequency methods. The ideality factor of the diode was found to be 5.41 and the obtained n value is higher than unity due to the interface states between the two semiconductor materials and series resistance. The reverse current of the diode strongly increases with illumination intensity of 100 mW cm(-2) and the diode gives a maximum open circuit voltage V(oc) of 0.12 V and short-circuits current I(sc), of 0.53 x 10(-6) A. The interface state density values for the diode were found to vary from 7.82 x 10(13) to 3.02 x 10(12) eV(-1) cm(-2) under various bias voltages. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Nanostructures; Nanomaterials; Oxides; Heterojunction semiconductor devices